Multivariate Cox regression analysis of prognostic genes and therapeutic mechanisms of gastric cancer - Yangyang Xiao; Zhiru Zhong; Chunli Yang; Zhiying Lin (Discover Oncology)
Abstract Gastric cancer (GC) is a common malignant tumor, which originated from the epithelial cells of the stomach. It has the characteristics of high incidence and poor prognosis. Therefore, it is urgent to find new prognostic markers for the diagnosis and treatment of GC. Download gene expression matrix and clinical data from TCGA database and GSE84437 dataset. Through independent prognostic analysis and clinical correlation analysis, 74 prognostic related genes (PRG) were screened out. A PPI network was established for PRG to identify four key genes (KG), namely LMOD1, CRYAB, VCL and MYL9. Survival analysis showed that patients with high expression of KG had poor prognosis. Multivariate Cox regression analysis showed that KG was an independent prognostic factor. TCGA database verifies the importance and significance of KG as a prognostic indicator. Functional enrichment analysis showed that KG was mainly involved in cell adhesion molecules, adhesion spots and PI3K/AKT signaling pathway. KG may be a potential therapeutic target for gastric cancer.